2017
DOI: 10.1513/annalsats.201612-1033fr
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Inefficiency and Exertional Dyspnea in Early Chronic Obstructive Pulmonary Disease

Abstract: Exertional dyspnea is present across the spectrum of chronic obstructive pulmonary disease (COPD) severity. However, without realizing it themselves, patients may decrease daily physical activity to avoid distressing respiratory sensations. Dyspnea also may be associated with deconditioning. Cardiopulmonary exercise testing can uncover exertional dyspnea and its physiological determinants in patients with preserved or only mildly reduced FEV. Dyspnea in mild COPD can largely be explained by increased "wasted" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 47 publications
4
32
0
1
Order By: Relevance
“…In COPD, ventilation-perfusion mismatch in the lung leads to inefficient pulmonary gas exchange. Dysfunction of the lung microvasculature occurs to a variable extent across the entire severity spectrum of COPD [27][28][29]. In mild COPD during exercise, physiological dead space, the ventilatory equivalent for CO 2 (V E /VCO 2 )-a measure of ventilatory efficiency-and alveolar ventilation (V A ) are all elevated, compared with healthy controls [27].…”
Section: Increased Inspiratory Neural Drivementioning
confidence: 99%
“…In COPD, ventilation-perfusion mismatch in the lung leads to inefficient pulmonary gas exchange. Dysfunction of the lung microvasculature occurs to a variable extent across the entire severity spectrum of COPD [27][28][29]. In mild COPD during exercise, physiological dead space, the ventilatory equivalent for CO 2 (V E /VCO 2 )-a measure of ventilatory efficiency-and alveolar ventilation (V A ) are all elevated, compared with healthy controls [27].…”
Section: Increased Inspiratory Neural Drivementioning
confidence: 99%
“…The 11 ± 3 pack‐years (the number of packs of cigarettes smoked per day, multiplied by years of consumption) intensity of smoking could cover up more severe pulmonary disease, because it was recently shown that smoking duration alone is more important to estimate chronic parenchymal pulmonary disease compared with pack‐years (Bhatt et al., ). Non‐COPD smokers can develop ventilatory constraints, gas trapping, dynamic hyperinflation (DH) and increased ventilatory inefficiency (Neder et al., ) besides dead‐space augmentation (Gläser et al., ). In a small sample such as this, ∼50% of smokers could well lead to very heterogeneous responses, partly explaining the strongly significant calculated expiratory reserve volume (ERV, as a percentage of predicted Forced Vital Capacity) and inspiratory capacity (IC, as a percentage of predicted) correlations with alveolar volume or dead‐space fraction of tidal volume, caused by a statistical ‘effect of the extremes’, supposing a worse superimposed detrimental effect of tobacco‐associated small airway disease.…”
mentioning
confidence: 99%
“…Importantly, the percent predicted physiological dead space of the HFrEF patients was substantially greater than that of the CTL participants during submaximal exercise (HFrEF, 134 ± 38% versus CTL, 96 ± 41%, P < 0.05). Furthermore, there and ventilatory constraints during exercise (Neder et al, 2017), this additional analysis indicates that HFrEF-induced pathophysiological mechanisms were largely responsible for the elevated physiological dead space compared with CTL participants. However, we do agree with Barbosa and Müller (2019) that future studies are necessary to determine how smoking history and/or duration influences the integrative cardiopulmonary response to exercise in HFrEF patients with and without concurrent COPD.…”
Section: Reply To Barbosa and Müllermentioning
confidence: 81%
“…Furthermore, there was a negative relationship between percent predicted physiological dead space and percent predicted IC during submaximal exercise in the HFrEF patients ( r = −0.74, P < 0.01), suggesting that ventilatory constraints contribute to the elevated physiological dead space in HFrEF patients when smoking status is accounted for. Although smoking history can have a negative influence on pulmonary function and ventilatory constraints during exercise (Neder et al., ), this additional analysis indicates that HFrEF‐induced pathophysiological mechanisms were largely responsible for the elevated physiological dead space compared with CTL participants. However, we do agree with Barbosa and Müller () that future studies are necessary to determine how smoking history and/or duration influences the integrative cardiopulmonary response to exercise in HFrEF patients with and without concurrent COPD.…”
mentioning
confidence: 79%